Actions of Bisnucleophiles on (E)-3-[3-(2-Hydroxyaryl)-3-oxoprop-1-en-1-yl]chromones: Versatile Transformations into Oxygen- and Nitrogen-Containing Heterocycles - Hassaine, Ridha (2017)
The transformations of (E)-3-[3-(2-hydroxyaryl)-3-oxoprop-1-en-1-yl]chromones in the presence of methylhydrazine and aromatic bisnucleophiles are described. The reactions generally lead to chromone ring transformation via pyrone ring-opening and heterocyclization to give novel diazoles and (Z)-3-aminomethylenechromanones, respectively. Piperazine catalyzes chromanone ring closure of the starting substrate to afford chromone-chromanone dyads.